Pedro Zulen y la estética: huellas de una filosofía no escrita - Yalán Dongo, Eduardo (2025)
This article explores the aesthetic dimension of Pedro Zulen’s thought, an aspect that has been little studied compared to his political and philosophical concerns. Based on a hermeneutic analysis of his texts, it examines his conception of expression and its relationship to image and sign in the aesthetic process. It discusses his critique of Bergson and his ambiguous assessment of poetry as a form of knowledge, identifying tensions between poetic intuition and the need for precise expression. The central hypothesis is that, in Zulen’s philosophy, poetry occupies an ambiguous place: it is criticized for its lack of contribution to rational knowledge, but also valued as a means of expressing the absolute. This ambivalence allows us to explore the place of the aesthetic in his thought.